2017
DOI: 10.1111/andr.12431
|View full text |Cite
|
Sign up to set email alerts
|

Surgical correction of Peyronie's disease via tunica albuginea plication: long‐term follow‐up

Abstract: Peyronie's disease (PD) is an acquired connective tissue disorder of the tunica albuginea with fibrosis and inflammation that lead to palpable plaques formation, penile curvature, and pain during erection. Patients report negative effects on main domains such as physical appearance and self-image, sexual function, and performance. The aim of this study was to evaluate plication of the albuginea outcomes after a long-term follow-up period. Between 1998 and 2006, a total of 204 patients with PD underwent surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
1
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
3
1
0
6
Order By: Relevance
“…Location of the plaque considerably differs across previous studies, being dorsal location the most frequent at disease onset ( Table 1 ) [ 18 19 20 21 ]. Similarly, deviation of erect penis is significantly changeable according to previous reports ( Table 2 ) [ 18 20 21 22 23 ]. Clearly, there might be some patients who traumatize their penis and, thus, develop a secondary curvature due to the inflammation process and loss of compliance.…”
Section: Natural Historysupporting
confidence: 68%
“…Location of the plaque considerably differs across previous studies, being dorsal location the most frequent at disease onset ( Table 1 ) [ 18 19 20 21 ]. Similarly, deviation of erect penis is significantly changeable according to previous reports ( Table 2 ) [ 18 20 21 22 23 ]. Clearly, there might be some patients who traumatize their penis and, thus, develop a secondary curvature due to the inflammation process and loss of compliance.…”
Section: Natural Historysupporting
confidence: 68%
“…Previous studies have demonstrated that penile shortening occurs in 41%–100% and 0%–40% of patients following various plication procedures and incision or partial plaque excision with grafting techniques, respectively. 18 25 26 27 Although penile shortening rarely results in intercourse difficulty, 28 patients often perceive that the loss of length is greater than the actual loss. 29 In our study, objective measurement of stretched penile length showed that the proportion of patients with shortening penile length and the degree of penile length loss were similar between patients who followed the doctor's recommendation and those who did not follow regardless of the type of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[132][133][134][135][136][137][138][139] La satisfaction post opératoire varie de 43 à 98,5% [128,133]. Néanmoins l'absence de standardisation de cette mesure rend l'interprétation difficile, Paez et al considèrent l'insatisfaction comme fréquente chez les patients opérés d'une maladie de Lapeyronie Après tout type de plicature 47,7 % à 94 % des patients ont des rapports sexuels satisfaisants [129,130,[133][134][135][136][137][138][139] et 66 % des partenaires sont satisfaits par l'intervention [129]. La récidive de la déformation varie de (2,1 % et 22,2 %) [132,[135][136][137][138].…”
Section: Résultatsunclassified
“…[131] Dans les 2 premières années suivant la plicature, l'apparition d'une DE ou l'aggravation d'une DE préexistante est faible le plus souvent [139][140][141][142][143][144][145], mais peut varier et s'aggraver avec le temps notamment avec l'apparition de facteurs de vieillissement physiologiques et l'apparition de facteurs de comorbidité, rendant l'interprétation des résultats difficiles. [123][124][125][126][127][128][129][130][131][132][133][134][135][136] Les noeuds sont fréquemment palpables après plicature (33,3 % à 81 %), mais peu souvent responsables d'une gêne (1,7 % à 6 %). Pour cette raison, les points peuvent être inversant et utiliser différents types de sutures résorbables et non résorbables.…”
Section: Conséquences Et Complicationsunclassified
See 1 more Smart Citation